Pelaksanaan Pembelajaran Seni Budaya (Musik) Kelas VIII di SMP Negeri 9 Pariaman - Annisa Febriani Sonia; Esy Maestro (SENDRATASIK UNP, 2021)
This study aims to find out and describe how the implementation of face-to-face and online learning in the subjects of cultural arts music material class VIII at SMP Negeri 9 Pariaman during the covid-19 pandemic. This type of research is qualitative research using descriptive methods of analysis. This research instrument is the researcher himself and assisted with supporting instruments such as stationery and mobile phones. Data collection techniques using interviews, library studies and documentation. The data types in this study are primary and secondary data. The steps of analyzing data are collecting data, identifying data, classifying data, describing data and concluding data. The results showed that the implementation of art learning music culture face-to-face and online with material singing traditional songs in class VIII. I SMP Negeri 9 Pariaman is less than maximum. In the implementation of time-limited face-to-face learning, teachers cannot optimally manage classroom learning, and cannot practice this material directly in front of students.  And the evaluation conducted by the teacher does not pay attention to whether the techniques and singing styles that students practice are correct or not. The media that teachers use in teaching in addition to using cultural art print books, teachers also use the Smart Learning application because this application does not use a lot of internet quota or does not have to use a good mobile network.